TIME, HISTORY AND CULTURAL SPACES ([S.l.])
1 online resource
Keywords: This book brings together critical essays on time, history and narrativity and the explorations of these concepts in philosophy, music, art and literature. The volume provides a comprehensive introduction to narrative theories as well as philosophical discourses on time, memory and the self. Drawing insights from western and eastern philosophy, it discusses themes such as subjectivity and identity in historical narratives, theorization of time in cinema and other arts and the relationship between the understandings of existence, consciousness and concepts such as Kala, Aion, and yugas. The book also looks at the narrativization of history across cultures by exploring modern fiction from China and India, murals of martyrs in Northern Ireland, music and films set against the canvas of the Second World War and the Holocaust, as well as diasporic cultural histories. This book will be an interesting read for scholars and researchers of comparative literature, history, philosophy of history, cultural studies and post-colonial studies.